2009
DOI: 10.1021/nl902788u
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Buffered Dielectric to Achieve High Field-Effect Carrier Mobility in Graphene Transistors

Abstract: We utilize an organic polymer buffer layer between graphene and conventional gate dielectrics in top-gated graphene transistors. Unlike other insulators, this dielectric stack does not significantly degrade carrier mobility, allowing for high field-effect mobilities to be retained in top-gate operation. This is demonstrated in both two-point and four-point analysis and in the high-frequency operation of a graphene transistor. Temperature dependence of the carrier mobility suggests that phonons are the dominant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
279
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(300 citation statements)
references
References 24 publications
16
279
4
1
Order By: Relevance
“…A 6-nm gate dielectric of HfO 2 is conformally grown by atomic layer deposition (ALD) at 150 °C yielding a dielectric constant of κ ≈ 13. 39 Large, single-crystals of graphene are grown by chemical vapor deposition (CVD) and transferred over the gate using well-established procedures. 30 Graphene is patterned with a second lithography step and reactive ion etching in an oxygen plasma.…”
Section: ρ Of the Substrate As ε = T/(2ρ)mentioning
confidence: 99%
“…A 6-nm gate dielectric of HfO 2 is conformally grown by atomic layer deposition (ALD) at 150 °C yielding a dielectric constant of κ ≈ 13. 39 Large, single-crystals of graphene are grown by chemical vapor deposition (CVD) and transferred over the gate using well-established procedures. 30 Graphene is patterned with a second lithography step and reactive ion etching in an oxygen plasma.…”
Section: ρ Of the Substrate As ε = T/(2ρ)mentioning
confidence: 99%
“…For example, it has been recently shown that electrons in monolayer FeSe can couple strongly with phonons in the adjacent SrTiO 3 substrate, which may play an important role in the anomalously high critical temperature for superconductivity in the system 21,22 . However, the unusual interlayer electron-phonon interactions in the van der Waals heterostructures have been little explored so far, although there have been indications that interlayer interactions between graphene electrons and the substrate phonons is a limiting factor for higher graphene electron mobility at room temperature 23,24 .…”
mentioning
confidence: 99%
“…However, the unusual interlayer electron-phonon interactions in the van der Waals heterostructures have been little explored so far, although there have been indications that interlayer interactions between graphene electrons and the substrate phonons is a limiting factor for higher graphene electron mobility at room temperature 23,24 .…”
mentioning
confidence: 99%
“…Non-covalent functionalization layer (NCFL) can be formed prior to ALD growth via molecules like DNA [62], 3,4,9,10-perylene tetracarboxylic acid (PTCA) [63], and NO 2 shown in Figure 4(b) [64][65][66][67]. Besides molecules, polymer can also play the role of NCFL, such as NFC polymers [54,68,69], and ozone pre-treatment (Figure 4(c)) is proved to work for ALD growth as well [70]. Moreover, directly constructing nucleation layer via oxidation of thin film of evaporated or sputtered Al (several nm), followed by Al 2 O 3 ALD growth, is also a choice to form dielectric on graphene surface [71,72].…”
Section: High-κ Dielectric Growth On Graphenementioning
confidence: 99%